Experimental validation of an analytical kinetic model for edge-localized modes in JET-ITER-like wall. (11th April 2018) - Guillemaut, C.; Metzger, C.; Moulton, D.; Heinola, K.; O'Mullane, M.; Balboa, I.; Boom, J.; Matthews, G.F.; Silburn, S.; Solano, E.R.
Abstract: The design and operation of future fusion devices relying on H-mode plasmas requires reliable modelling of edge-localized modes (ELMs) for precise prediction of divertor target conditions. An extensive experimental validation of simple analytical predictions of the time evolution of target plasma loads during ELMs has been carried out here in more than 70 JET-ITER-like wall H-mode experiments with a wide range of conditions. Comparisons of these analytical predictions with diagnostic measurements of target ion flux density, power density, impact energy and electron temperature during ELMs are presented in this paper and show excellent agreement. The analytical predictions tested here are made with the 'free-streaming' kinetic model (FSM) which describes ELMs as a quasi-neutral plasma bunch expanding along the magnetic field lines into the Scrape-Off Layer without collisions. Consequences of the FSM on energy reflection and deposition on divertor targets during ELMs are also discussed.